Cimahi’s Parallel Diplomacy in Developing Cultural Tourism in Kampung Adat Cireundeu - Zahra, Mayra Zahabiya; Azmi, Fuad (Dinasti Research, 2026)
This article examines how parallel diplomacy is practiced by the Cimahi City Government in developing tourism in Kampung Adat Cireundeu, a traditional village in West Java. In contemporary international relations, subnational actors and local communities increasingly engage in international activities to pursue their regional interests. Despite its cultural potential, tourism development in Kampung Adat Cireundeu still faces challenges related to promotion and limited international exposure. This research aims to analyze the forms of parallel diplomacy and to examine the roles of governmental and societal actors in supporting tourism development. The research employs a qualitative approach using semi-structured interviews with 6 key informants from government officials, indigenous community members, tourism actors, and visitors, supported by document analysis and digital research. The findings show that parallel diplomacy in Cimahi remains at an early stage and mainly occurs through exploratory interactions rather than formal international cooperation. Meanwhile, the indigenous community of Kampung Adat Cireundeu facilitates international interaction through cultural tourism activities, highlighting the importance of collaboration between local governments and community actors. These findings imply the need for stronger institutional support and strategic collaboration to enhance international exposure and sustainable tourism development.